New media futures : the rise of women in the digital arts - Cox, Donna J.; Sandor, Ellen; Fron, Janine (University of Illinois Press, 2018)
"This project captures the spirit and contributions of women working in digital arts media and education in the Midwest--a region that, beginning in the mid-1980s, established itself as a center for the technological revolution. Bringing together historical research and interviews with key participants in the development of digital arts, this volume explores seminal events at the University of Illinois and the School of the Art Institute in Chicago that led to the establishment of interdisciplinary Renaissance Teams in advanced academic computing communities, which created a bridge to the humanities and to Chicago's emerging art scene. Digital games, virtual reality, supercomputing graphics, and internet, browser-based art all evolved during this revolution, underscored by the region's history of widespread social change and artistic innovation, and women artists and computing experts were integral to the development of these new media. Spurred by a dynamic of social feminist change, these events fostered an atmosphere of creative expression, innovation, interdisciplinary collaboration, while crossing gender lines and incorporating an artistic approach in a scientific environment. Ultimately, these events ushered in the digital age and paved the way for social media, which was both a product and a result of the confluence of the social relationships and human relationships nurtured by digital arts exploration in the region"--